Composição química e rendimento de resíduos da indústria de filetagem de Tilápia do Nilo (Oreochromis niloticus) - Viera Júnior, Leonardo (2013)
World production of fish grows every year . The set technology , the performance and features suitable for cultivation , make Nile tilapia produced most of the species in Brazil and worldwide. Despite the high growth performance tilapia has been little or underutilized in terms of processing. With an average use only 35 % of its composition in the filleting industry . Full use of the product is shown an alternative for developing the activity , and contribute to the improvement of the environment, since these residues are mostly discarded without any treatment. The aim of this study was to evaluate the chemical composition and yield CMS industry waste filleting . 5 were chosen for both types of waste . The residues were: head, titties , belly , casting and V-cut fillet . All selected residues were chosen because they have interesting characteristics for industrial processing , or by the possibility of using byproducts resulting in main product , in this case the fillet , for use as or in animal feed byproducts . For this study, analyzes were performed on CMS performance of waste in relation to its weight and initial analysis to determine their chemical composition . Among the residues evaluated what stood out in terms of yield and composition was cut into the fillet V , with similar composition and fillet yield of 90 % . Other wastes as substrate and peitinho proved attractive from the point of view of performance for the industry, since presented in CMS yield exceeding 50%. These residues are those with the highest volume in the slaughter plant a filleting industry . The cutting head good productions , but was not visually appealing . Cutting belly was the only one who had a yield of CMS lower and higher loss during the process . This fact shows that this may not be the most suitable method for the preparation of CMS from this residue. With this study it was concluded that the use of industrial waste tilapia filleting is critical to leverage the success of the activity. The use of parts before " rejected " during the generation of co-products and by-products and improve the utilization contributes to not degrade the environment. From the standpoint of yield analysis all waste except , cutting belly showed adequate use.